Effect of cooking methods and cooking oils on color, texture and antioxidative properties of brown rice - Chen, Jia Ling (2023)
Brown rice consumption is in continuing trends due to its health-promoting features. Effects of cooking on physical and antioxidative properties of brown rice were investigated by applying three different cooking methods involving steaming (40 mins) and/or frying (1 min) with/without palm and coconut oils. For color measurement, lightness (L*) of control was significantly decreased in cooking methods I and II. Addition of palm and coconut oils did not significantly affect a* and b* of treated rice in all cooking methods. With the control as a reference, there was an insignificant (p > 0.05) difference between total color differences of oil-treated rice. Furthermore, results of texture analysis reported a significant (p < 0.05) decrease in hardness and increase in stickiness of control in cooking methods I and II. However, in cooking methods I and II, oil addition significantly increased hardness and decreased stickiness of treated rice. For determination of antioxidative properties, total phenolic contents (TPC) and total flavonoid contents (TFC) of cooked brown rice were evaluated. Results of TPC and TFC of cooked rice that were respectively examined by Folin-Ciocalteau’s test and aluminium chloride colorimetric methods demonstrated that cooking methods I and II significantly reduced antioxidant contents of control. Nevertheless, in cooking methods I and II, palm oil treated iii rice had significantly higher TPC and TFC than coconut oil treated rice and control. Lastly, antioxidant activity was studied by DPPH and reducing power assays and interpreted as IC50 and EC50, respectively. Inverse proportion between TPC and TFC with IC50 and EC50 values corroborated the lower IC50 and EC50 values of palm oil treated rice with higher antioxidant activity in cooking methods I and II. Therefore, treating brown rice with palm oil using cooking methods I and II was recommended, due to the firmer texture, and its high antioxidant contents and activities.